2013
DOI: 10.1002/bit.25153
|View full text |Cite
|
Sign up to set email alerts
|

Controlled local presentation of matrix proteins in microparticle–laden cell aggregates

Abstract: Multi-cellular aggregates are found in healthy and diseased tissues, and while cell-cell contact is important for regulating many cell functions, cells also interact, to varying degrees, with extra-cellular matrix (ECM) proteins. Islets of Langerhans are one such example of cell aggregates in contact with ECM, both at the periphery of the cluster and dispersed throughout. While several studies have investigated the effect of reintroducing contact with ECM proteins on islet cell survival and function, the major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…Several proof-of-concept studies have demonstrated the possibility of using biomaterial-based microparticles to modulate the 3D microenvironment of stem cell aggregates [40, 41]. However, successful induction of PSC aggregate differentiation toward specific lineages through this strategy has yet to be reported.…”
Section: Discussionmentioning
confidence: 99%
“…Several proof-of-concept studies have demonstrated the possibility of using biomaterial-based microparticles to modulate the 3D microenvironment of stem cell aggregates [40, 41]. However, successful induction of PSC aggregate differentiation toward specific lineages through this strategy has yet to be reported.…”
Section: Discussionmentioning
confidence: 99%
“…Based on this principle, by introducing specific structural and molecular elements in varying geometries and at different concentrations, a range of biomaterials with tissue-specific structural properties and bioinspired polymeric surface close to those of the native ECM can be created [687,688]. Upon application, penetrating cells may be surrounded by a dynamic pericellular matrix, similar to a native matrix, that possesses considerable regulatory potential [689692]. This approach is spurring interest in the use of natural ECM proteins for scaffolding production.…”
Section: Future Directions and Outlookmentioning
confidence: 99%
“…However, the mechanism that leads to protein misfolding and aggregation is not common for all proteins [ 8 ]. In recent years, studies have revealed several ways to suppress the aggregation processes by different group of molecules or compounds which include metal ions, acridine and its derivatives, polyphenols, plant derivatives, drug molecules and various chemical agents [ 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. In all these studies, research has mainly been directed to develop the anti-amyloidogenic or anti-aggregating compounds by studying their effect either on proteins directly involved in neurological and non-neurological disorders [ 16 ] or on model proteins having similarity with the them [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%